Kelayakan Usahatani Ubi Jalar dengan Penerapan Teknologi Pengguludan di Lahan Kering Masam di Lampung - Prasetiaswati, Nila; Radjit, Budhi Santoso (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
An experiment was carried out at Natar Experiment Station, South Lampung, from March to June 2010. The objective of the research was to identify technical and economic feasibilities of sweet potato farming system on a dry acid soil using improved ridging technology. The technologies tested were: (1) use of large ridges (60 cm high) with a 125 cm x 20 cm plant spacing without breaking down the ridges, and (2) use of small ridges (30 cm high) with a 100 cm x 25 cm plant spacing and followed by breaking down the ridges, and the common farm practice as control. Sweet potato varieties Sawentar and local Kuning Banyuwangi were used in this experiment. The fertilizers applied in the improved technologies were at rate of 300 kg urea + 200 kg SP36 + 100 kg KCl + 500 kg dolomite + 4 t manure per ha. Results of the experiment showed that yields of sweet potato varieties grown on large ridges were higher than those grown on the small ridge. Variety Sawentar that was grown on large ridges yielded 18.68 t/ha and on small ridges 14.43 t/ha fresh tubers, with benefits of Rp 16,090,000 (B/C ratio 2.22) dan Rp10,987,500 (B/C ratio 1.56) respectively. The local variety Kuning Banyuwangi produced lower yield than that of Sawentar on both of the improved technology with B/C ratios less than 1.0. Variety Sawentar that was grown on the small ridge gave MBCR up to 3.09, hence this technology could be recommended to be applied in the dry land acid soil.